Observations on ruminant fat metabolism with particular relation to lactation : a thesis presented in partial fulfilment of the requirements for the degree of M. Agr. Sc. of the University of New Zealand - Mayhead, J W (Massey University, 1949)
In that animal fat is a major economic "building block" the mechanism of its production has attracted particular study. Although observations regarding digestion of fats may be traced back as far as those of Asellius in 1622 it was in 1843 that specific investigations into body fat production were first instituted by Lawes and Gilbert. From 1900 onwards biochemical research has made its greatest advances but, in spite of the volume of literature published on the subject of fat metabolism the state of knowledge in this field may yet be in its infancy. The three main experiments to be described relate principally to the changes effected in the degree of unsaturation of milk fat from dairy cows when highly unsaturated oils are included in the daily ration. The immediate effects of short-term inanition are also investigated. Two minor experiments are described; the first concerning the tracing of ingested stained fat into the milk and depot fats of simple-stomached animals; the second relation to the keeping qualities of milk fats of varying degrees of unsaturation.
Keywords: Fat; Lactation; Dairy cattle; Metabolism